Analisis Fraud Diamond Theory dalam Mendeteksi Terjadinya Manajemen Laba pada Laporan Keuangan Perusahaan - Khairi, Himmatul; Alfarisi, M. Fany (Jurnal Manajemen, 2019)
In this paper, we discuss the elements of fraud diamond theory against indications of earnings management in Indonesia's financing firms for the year 2014 to 2018. The independent variables are financial stability, institutional ownership, audit quality, effective monitoring, auditor changes, ratio total accruals to total assets, change of directors, and independent board of commissioners, while the dependent variable used is the manipulation of financial statements proxied by earnings management. This study used 75 samples taken from 15 companies listed on the Indonesia Stock Exchange in 2014-2018. This research was conducted with quantitative methods using secondary data. Data analysis uses multiple regression models based on panel data, using firm size, leverage and firm age as a control variable. The results indicate that there are three important variables in the analysis of financial manipulation, those are financial stability, ratio total accruals to total assets, and a number of independent commissioners. These variables represent three elements in the diamond fraud theory, financial stability which is presenting pressure, ratio total accruals to total assets representing rationalization, and a number of independent commissioners presenting competency.